2016
DOI: 10.1111/1348-0421.12458
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual immunization with Japanese encephalitis virus vaccine effectively induces immunity through both cellular and humoral immune responses in mice

Abstract: The Japanese encephalitis virus (JEV) is the leading cause of viral encephalitis. Although there are four classes of vaccines against JEV, all of them are administered by s.c or i.m injection. Here, the effectiveness of sublingual (s.l.) administration of a JEV live-attenuated vaccine or recombinant modified vaccinia virus Ankara (MVA) vaccine, including JEV prM/E, was investigated. The mice were immunized three times i.m. or s.c. One week after the final immunization by both s.l. and i.m. routes, the titers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…At 35 dpi, rVTT-CE1-JE-EGFP PRNT was 1:267, and there was no significant difference compared with that of the SA14-14-2 group. Previous studies reported that immunized mice produced PRNTs similar to the results of this study (Nam et al 1999), and suggested that PRNTs (1:160) are sufficient to completely protect mice against a JEV challenge (Lee et al 2016). Sera cytokine levels and CD3 + CD4 + and CD3 + CD8 + T lymphocytes percentage in the rVTT-CE1-JE-EGFP group were significantly higher than those in the rVTT-EGFP ( p < 0.01) and PBS ( p < 0.01) control groups, but there was no significant difference compared with those of the SA14-14-2 group, thus indicating that rVTT-CE1-JE-EGFP effectively induced humoral and cellular responses.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…At 35 dpi, rVTT-CE1-JE-EGFP PRNT was 1:267, and there was no significant difference compared with that of the SA14-14-2 group. Previous studies reported that immunized mice produced PRNTs similar to the results of this study (Nam et al 1999), and suggested that PRNTs (1:160) are sufficient to completely protect mice against a JEV challenge (Lee et al 2016). Sera cytokine levels and CD3 + CD4 + and CD3 + CD8 + T lymphocytes percentage in the rVTT-CE1-JE-EGFP group were significantly higher than those in the rVTT-EGFP ( p < 0.01) and PBS ( p < 0.01) control groups, but there was no significant difference compared with those of the SA14-14-2 group, thus indicating that rVTT-CE1-JE-EGFP effectively induced humoral and cellular responses.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we constructed a recombinant VACV that expresses JEV E and CHIKV E1 proteins with the VACV TianTan E3L deletion mutant, rVTT-CE1-JE-EGFP. With regard to JEV vaccine, specific antibodies significantly increased, as previously reported (Lee et al 2016). At 35 dpi, JEV-specific antibodies in the rVTT-CE1-JE-EGFP group were significantly higher than those in the rVTT-EGFP and PBS control groups ( p < 0.01), but there was no significant difference as compared with the SA14-14-2 group.…”
Section: Discussionsupporting
confidence: 83%
“…The elicitation of T cell mediated immune responses and their long-term duration are not well understood yet. It has been shown that sublingual immunization with the live attenuated SA14-14-2 in mice induces JEV-specific IFN-γ + CD4 + and CD8 + T cell responses [54]. In one clinical study in South India [55], T cell responses were evaluated following vaccination of 15 adults with a single dose of JEV live-attenuated vaccine SA14-14-2.…”
Section: Role Of T Cells In Host Immunity Against Flavivirus Vaccinesmentioning
confidence: 99%
“…As the number of CD45 + IL-4 + cells did not show any decrease ( Fig 7Cb ), polarization of the culture in the Th-1 direction was not confirmed. A mixed Th1/Th2 response was also induced after immunization of BALB/c mice with chimeric VLPs prepared by insertion of a short epitope at four different sites in the yeast-expressed hamster polyomavirus major capsid protein VP1 [ 70 ] and in the mouse model of vaccination by a JEV (Japanese encephalitis virus) live-attenuated vaccine or recombinant modified vaccinia virus Ankara [ 71 ]. However, in both models, the proportion of Th1/Th2 population was established according to the immunoglobulin subclass distribution.…”
Section: Resultsmentioning
confidence: 99%